A modeling framework for manufacturing services in Service-oriented Holonic Manufacturing Systems. (October 2016) - Gamboa Quintanilla, Francisco; Cardin, Olivier; L'Anton, Anne; Castagna, Pierre
Abstract: Holonic and Service-Oriented Architectures have been proposed as solutions for the conception of flexible and reactive systems. The combination of both architectures has been recognized as an attractive solution for the conception of more flexible and reactive systems. Services, originally conceived for web applications, need new models that better adapt to the needs of manufacturing systems namely, the specification and planning of processes. This paper proposes a methodology for designing customizable product-process specifications based on manufacturing-services that are suitable for product driven applications. A framework is proposed for modeling manufacturing-services designed for its application in Holonic Manufacturing Systems, preserving the fractal character found in products and processes. Three types of manufacturing processes are identified based on the relations among its composing operations and a model is proposed for each type. Application service-ontologies are created to describe operations and resource capabilities rather than complex semantic descriptions to facilitate process design and reduce the computational load of service discovery for planning. The framework leverages service reusability among process families in the same way as physical features are reused among product families. An illustrative example describes the design of a product's process specification based on the manufacturing service framework in a Holonic Manufacturing System, giving rise to Service-oriented Holonic Manufacturing Systems. Highlights: A framework for designing Manufacturing Services (MServices) is proposed. Service-oriented Holonic paradigm fosters flexibility in manufacturing control. MServices is the main communication primitive in distributed control systems. Automatic discovery of process capabilities is made possible with MServices. SoHMS formalism enables plug and produce and reusability principles.